Biological mechanisms of invasive algae and meta-analysis of ecological impacts on local communities of marine organisms - Huili Li; Yaqi Geng; Haowei Shi; Chao Wu; Zhen Yu; Hongxia Zhang; Lihong Chen; Ronglian Xing (Ecological Indicators, 2023)
The frequent invasion of organisms poses a serious threat to biodiversity, ecosystem service functions, and economic development. Invasions from terrestrial systems have been well studied, but invasions from marine systems still lack a literature review, especially for invasive algae. With the frequent invasion of non-native algae, marine biodiversity and its sustainable use are threatened, and thus, the in-depth investigation of the biological mechanisms and ecological impacts of invasive alien marine algae has become particularly important. Here, we conducted a literature review of a series of studies that were undertaken by identified experts on algae invasions, including information on the classification of invasive algae in the ecosystem, mechanisms of invasion success (including the invader’s biological traits, interactions with native species, and adaptive evolution), and the impact on the native community and environment of the invaded area. In addition, we put forward suggestions for relevant research on invasive algae to overcome the current obstacles and provide references for future research on invasive marine algae. This review could be used to inform biological regulations and provides a scientific basis for the protection of marine biodiversity, sustainable environmental development, and the restoration of blue carbon ecosystems.